Rainfed farming prospects in the low rainfall zone of northern Iraq based on meteorological and soil moisture measurements - Hussein, Mohammad Hasan (Journal of Aridland Agriculture, 2017)
Â More than 50% of the rainfed region in northernIraqfalls within the low rainfall zone receiving between 300 and 400 mm of mean seasonal rainfall. Several natural runoff plots with access tubes were used to measure soil moisture distribution in depth and time. Measurements during two consecutive rainfall seasons were used to forecast the rainfed farming prospects in the low rainfall zone. The first season is considered wet because it received 568 mm of mean seasonal rainfall; the second rainfall season is considered dry because it received 256 of mean seasonal rainfall. The prospects of tillage systems, fertilization and soil moisture conservation for a successful rainfed farming (wheat and barley crops) venture in the low rainfall zone were explored and Â a rainfed farming guide for this zone was suggested.Â Â